Carbon nanotube/boehmite-derived alumina ceramics obtained by hydrothermal synthesis and spark plasma sintering (SPS) - Zaman, Ali Can; Ustundag, Cem B.; Celik, Ali; Kara, Alpagut; Kaya, Figen; Kaya, Cengiz (ELSEVIER SCI LTD, 2010)
Preparation, structure and properties of hydrothermally treated carbon nanotube/boehmite (CNT/gamma-AlOOH) and densification with spark plasma sintering of Al2O3 and CNT/Al2O3 nanocomposites were investigated. Hydrothermal synthesis was employed to produce CNT/boehmite from an aluminum acetate (Al(OH)(C2H3O2)(2)) and multiwall-CNTs mixture (200 degrees C/2 h.). TEM observations revealed that the size of the cubic shape boehmite particles lies around 40 nm and the presence of the interaction between surface functionalized CNTs and boehmite particles acts to form 'nanocomposite particles'. Al2O3 and CNT/Al2O3 compact bodies were formed by means of spark plasma sintering (SPS) at 1600 degrees C for 5 min using an applied pressure of 50MPa resulting in the formation of stable alpha-Al2O3 phase and CNT-alumina compacts with nearly full density. It was also found that CNTs tend to locate along the alumina grain boundaries and therefore inhibit the grain coarsening and cause inter-granular fracture mode. The DC conductivity measurements reveal that the DC conductivity of CNT/Al2O3 is 10(-4) S/m which indicate that there is a 4 orders of magnitude increase in conductivity compared to monolithic Al2O3. The results of the microhardness tests indicate a slight increase in hardness for CNT/Al2O3 (28.35 GPa for Al2O3 and 28.57 GPa for CNT/Al2O3). (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Al2O3; Carbon nanotube; Hydrothermal synthesis; Spark plasma sintering; REINFORCED SILICON-CARBIDE; MATRIX COMPOSITES; MICROSTRUCTURE; Materials Science